From Dystopia to Realism: Emotions, Cultures and Imaginaries of Contemporary TV Seriality - Mario Tirino (Funes)
Why has television seriality begun to acquire an increasingly central role in the cultural consumption and media consumptions of millions of people, with its impact becoming more evident since the 2010s? Among the many analyses addressing this question, one of the most well-founded examines the connection between the distribution modes of platformized seriality and the temporality experienced by millions of young people and adults worldwide.